Challenging Interpretation of Blistering Patch Test Reaction in Hair Dye Induced Allergic Contact Dermatitis with Cross-Reaction: A Case Report - Ho Wen Chung; How Kang Nien; Nurafiqah Farhana Muhammad Yazid (UPM Press, 2026)
Indexed by Scopus